An Analysis of Acceleration and Speed Performances Through the Positions in Handball - Cengiz Taşkın,; Ali Kemal Taşkın, (Journal of Educational Issues, 2024)
This research was conducted in order to compare the acceleration and speed performances of handball players according to their positions. A total of 60 male handball players that includes 5 goalkeepers, 15 middle playmakers, 7 right playmakers, 8 left playmakers, 7 right wingers, 8 left wingers and 10 pivots who actively play handball in the 2nd league of the Turkish handball federation has participated in the study voluntarily. Average age of the subjects participating in the study is determined as 19.5±1.43 for the goalkeepers, 19.3±1.35 for the right-left playmakers, 18.7±1.29 for the right-left wingers, 19.1±1.89 for the pivot players. Acceleration and speed performances of the subjects were measured in accordance with the measurement technique and all the data obtained were analyzed in the SPSS 20.0 software package program. Results that is obtained is examined, it is seen that the best values in terms of acceleration and speed performance were the performance values of right-left playmakers and right-left wing players, while the worst performance values belonged to pivot players. As a result of our study, it was observed that athletes have different physical performances in handball according to their playing positions.